Experimental verification of the of contamination reduction of silicon during electron beam melting due to the use of a gas-dynamic window. Issue 1 (February 2021) - Kravtsov, A; Chikvaidze, G
Abstract: Metallurgical process of producing initial rods for FZ silicon single crystal application was described before. Purity of pulled ingots was satisfied, but some impurities level was over required level. Concentrations of these impurities such Fe; Cr; Cu; Al; O2 been decreased by gas dynamic window and electric trap in laboratory scale equipment. Present article described results of experiments on industry scale equipment with application gas dynamic window for purifying indicated impurities in initial rods and results received in FZ silicon single crystals, grown from that rods, for concentrations of Aluminum and Oxygen.